Coordination Abilities in Volleyball - Jaromir Šimonek (De Gruyter, 2014)
The author presents a general view on sports training, its eriodization and the role of coordination in the initial stages of preparation in volleyball. He also deals with inter-gender differences in levels of such abilities, describing motor tests for the assessment of coordination potential and providing the reader with standards for the development of talented players. Based on the nature of volleyball, the author analyses key features of sports performance. Coordination abilities, especially in the period of puberty, play an important role in the creation of coordination basis - prerequisites for the development of physical fitness and acquisition of motor skills. Based on the results of his own research, as well as studies conducted by international sports scientists, he offers a model for the development of coordination abilities in volleyball. This method is recommended for coaches to improve their professional work in volleyball classes and schools, and in sports clubs. In the long-term, application of the proposed model should contribute to the improvement of players' performance in competition.